Filling the Gap: The Consequences of Collaborator Loss in Corporate R&D - Felix Poege; Fabian Gaessler; Karin Hoisl; Dietmar Harhoff; Matthias Dorner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We examine how collaborator loss affects knowledge workers in corporate R&D. We argue that such a loss affects the remaining collaborators not only by reducing their team-specific capital (as argued in the prior literature) but also by increasing their bargaining power over the employer, who is in need of filling the gap left by the lost collaborator to ensure the continuation of R&D projects. This shift in bargaining power may, in turn, lead to benefits, such as additional resources or more attractive working conditions. These benefits can partially compensate for the negative effect of reduced team-specific capital on productivity and influence the career trajectories of the remaining collaborators. We empirically investigate the consequences of collaborator loss by exploiting 845 unexpected deaths of active inventors. We find that inventor death has a moderate negative effect on the productivity of the remaining collaborators. This negative effect disappears when we focus on the remaining collaborators who work for the same employer as the deceased inventor. Moreover, this group is more likely to be promoted and less likely to leave their current employer.
Keywords: 330; collaboration; mobility; innovation; inventors; patents; teams